If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -3(-5x + -17) = 17 Reorder the terms: -3x + -3(-17 + -5x) = 17 -3x + (-17 * -3 + -5x * -3) = 17 -3x + (51 + 15x) = 17 Reorder the terms: 51 + -3x + 15x = 17 Combine like terms: -3x + 15x = 12x 51 + 12x = 17 Solving 51 + 12x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-51' to each side of the equation. 51 + -51 + 12x = 17 + -51 Combine like terms: 51 + -51 = 0 0 + 12x = 17 + -51 12x = 17 + -51 Combine like terms: 17 + -51 = -34 12x = -34 Divide each side by '12'. x = -2.833333333 Simplifying x = -2.833333333
| -4h+16=22+2 | | 12+2(3p-4)=22 | | 11-6m-20=20-5m | | 5x+3=6x-14 | | 3b+2(b-3)=91.50 | | 8x-(-2+3)=11 | | 1/4(x-4)+x=14 | | 6x-12-3=x+27-9x | | 5/10+7/3 | | (2x-3)(x^3-x^2+3x+5)=0 | | 2x-2x+3=8 | | 72/x=8 | | 7=6q/4+8/4 | | 7*x=49 | | R-1/2(4R+2)=0 | | 80/x=8 | | x^3+14x^2-9x-324=0 | | 2x+x+4+x+x+x-x-3=92 | | 2(r+1)=9 | | -6.3(x+3.7)+7.65x=-1.1x-38.99 | | 2x/5=-8 | | 7x-14y=7 | | 7x+-14y=7 | | f-8-3f=37f+4 | | 3y-3=5y-5 | | f-8-3f=3-7f | | 84-3=6y+17 | | 11x=7x-20 | | 23-x=22 | | (2x+1/3)^2=0 | | 55=(3x-1)(5) | | 2(2k-5)-k=4-(3k+7) |